Comparison between Special Judo Fitness Test, metabolic variables and energy contribution in young judo athletes - Foresti, Yan F.; Bertucci, Danilo R. [UNESP]; Carvalho, Carlos D. de; Kalva-Filho, Carlos A. [UNESP]; De Andrade, Vitor L. [UNESP]; Barbieri, Ricardo A.; Bonagamba, Tito J.; Papoti, Marcelo (Int Scientific Information, Inc, 2020)
Background and Study Aim: Judo has been characterized as a high-intensity intermittent combat sport. The study's purpose is answer the question whether Special Judo Fitness Test (SET) variables are capable of discriminate young judo athlete's performance at different ages, and comparing the test with metabolic indicators and energy contribution. Material and Methods: Twenty-seven athletes were divided according to their ages: 10 to 12 years (G(10-12)), 13 to 14 years (G(13-1)(4)), 15 to 17 years (G(15-17)), and comparing with a control group (G(>18)). The Athletes were submitted to SJFT, before and immediately after the test, their oxygen consumption and blood lactate samples were collected for estimating energy contributions. The athletes and their parents gave consent for the study's participation Results: No significant differences were observed in the SJFT variables among groups, with the exception of the relative index, founding statistical differences between the G(10-12) with the other groups. Comparing the control group with the groups G(10-12), G(13-14), G(15-17), were found significant differences in the aerobic metabolism, aerobic power and anaerobic variables as lactate peak and anaerobic metabolism, indicating which the groups were physiological differents. Were found significant correlations between SJFT index and both (i) anaerobic alactic contribution for G(15-17) and (ii) anaerobic lactic contribution for G(>18). The test presents anaerobic predominance in the G(>18) and G(15-17), group. Conclusions: For utilization of the SJFT in young athletes we recommend use the relative index is a strategy to discriminating judo athletes of different ages and different physiological characteristics rather the traditional index.
Keywords: age-related; anaerobic fitness; combat sports; youth